New Evidence on Learning Trajectories in a Low-Income Setting - Bau, Natalie; Das, Jishnu; Chang, Andres Yi (World Bank, Washington, DC, 2021)
Using a unique longitudinal data set collected from primary school students in Pakistan, this paper documents four new facts about learning in low-income countries. First, children’s test scores increase by 1.19 standard deviation between Grades 3 and 6. Second, going to school is associated with greater learning. Children who drop out have the same test score gains prior to dropping out as those who do not but experience no improvements after dropping out. Third, there is significant variation in test score gains across students, but test scores converge over the primary schooling years. Students with initially low test scores gain more than those with initially high scores, even after accounting for mean reversion. Fourth, conditional on past test scores, household characteristics explain little of the variation in learning. To reconcile the findings with the literature, the paper introduces the concept of “fragile learning,” where progression may be followed by stagnation or reversals. The implications of these results are discussed in the context of several ongoing debates in the literature on education in low- and middle-income countries.